(untitled) (Journal Of Educational and Psychological Researches, 2017)
Marriage outside the court is a manifestation of the oppression that women are subjected to in Iraq its seriousness comes out of the consequences that it leads to The. It overlooks the age of the girl and her marriage in younger age or coerced to marry as it leads to neglecting the affordability of marital relationship as long as the marriage does not have any legal or material consequences. The present study aims to detect Characteristics of both wives, husbands and families Who agree to marry her daughters outside the court. And the reasons that lead them to marry outside the courts. It also aims to provide information on the circumstances of marriage and reasons for refusing to ratify it in court. The study was based on the sample social survey. And study sample included 300 women married outside the court. Who have been directed to the non - governmental organizations support centers in Sadr City for help. The main tool for this research is the questionnaire. The main findings of the study 1. Marriage outside the court is related to the marriage of children and more from 58% of the the sample Have been married before Their attainment Legal age status For marriage, 2 - Approximately half of the marriages which are concluded outside the court (48%) Do not continue and end in Divorce, separation, abandonment or the death of a spouse, 3- Low educational level is the dominant feature for wives and for couples and fathers and mothers of married women outside the court. 4. The decision to marry the girl taken by father often , and nearly 32% of women who were married outside the court had not taken their views or consent waver on marriage, And that a quarter of marriages concluded outside the court are forced marriages were coerced. 5. The 13% of marriages entered into outside the court marriages are not allowed by law and harmful practices associated with women (marriage as blood money or to stay under relative mandate). And 20% of married women outside the court are second or a third wives. 6 - Lack of interest in the civil contract by parents was the first reason behind the marriage outside the court. Followed by the complex procedure for marriage within the court. The promise to ratify the marriage came later in the third order. As for the young woman’s age came fourth in order . 7- Marriages were attributed to non - certified in court and face the risk of general collapse, dismantling the marital bond 36.3%. The husband ’s failure to ratify the marriage of the most important reasons not to ratify these marriages from the point of view of women, followed by the arrangement in terms of lack of interest in the ratification of marriage then comes not reaching the wife to the legal age of marriage , which will allow the ratification third place